2014
DOI: 10.1007/s11605-014-2591-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio Improves TNM and Astler-Coller’s Assessment of Colorectal Cancer Prognosis: an Analysis of 761 Node Positive Cases

Abstract: LNR is a powerful prognosis predictor, easily integrated with TNM and AC classifications to improve prognosis assessment and facilitate clinical use. Possible confusing factors should be considered in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
0
18
2
Order By: Relevance
“…Costi et al . also reported that the LNR was superior to the TNM classification in colorectal cancer, but their patient cohort differed from the present study in that they included both colon and rectal cancer patients. They divided their group into LNR1 and LNR2 based on a cut‐off point of 0.15 and used an arbitrary method to determine the cut‐off point based on the 75th percentile, having originally divided the group into quartiles.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Costi et al . also reported that the LNR was superior to the TNM classification in colorectal cancer, but their patient cohort differed from the present study in that they included both colon and rectal cancer patients. They divided their group into LNR1 and LNR2 based on a cut‐off point of 0.15 and used an arbitrary method to determine the cut‐off point based on the 75th percentile, having originally divided the group into quartiles.…”
Section: Discussioncontrasting
confidence: 57%
“…In a systematic review Ceelen et al [26] reported that the LNR was superior to the number of positive nodes, but comparison of N1/N2 with the LNR was limited owing to heterogeneity in the included studies. Costi et al [27] also reported that the LNR was superior to the TNM classification in colorectal cancer, but their patient cohort differed from the present study in that they included both colon and rectal cancer patients. They divided their group into LNR1 and LNR2 based on a cut-off point of 0.15 and used an arbitrary method to determine the cut-off point based on the 75th percentile, having originally divided the group into quartiles.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The cumulative 5-year survival rate was 63 % for patients with 1–3 positive node whereas 0 % for those with ≥4 positive nodes. LNR, another node-associated factor, has drawn much attention for predicting the survival outcome in patients with various gastrointestinal malignancies [ 16 , 17 , 19 21 ]. LNR may to some degree compensate or standardize variations in inadequate surgical lymph node dissection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive lymph node ratio (PLNR), the ratio of the number of positive lymph nodes to the total number of dissected lymph nodes, has been proposed as an independent prognostic factor in several solid cancers [6,7,8]. In a series of 353 ESCC patients, He et al [9] described the PLNR as an important predictor of OS after radical esophagectomy.…”
Section: Introductionmentioning
confidence: 99%